2021
DOI: 10.1002/cc.20483
|View full text |Cite
|
Sign up to set email alerts
|

Supporting undocumented community college students

Abstract: Community colleges are a critical access point to higher education for undocumented students, yet undocumented community college students often report feelings of constrained inclusion due to the limitations created by their citizenship status (Negrón-Gonzales, 2017). In this article, we review existing research on undocumented students in 2-year colleges, discussing the policies and practices that can be implemented to support undocumented community college students. Supportive policies include tuition and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Higher education institutions also need to consider their own institutional policies and how they support undocumented students (Enriquez et al, 2019). With respect to the community college setting, specific recommendations for practice include flexible course offerings and requirements, access to clear and guiding information, access to psychological services that support undocumented students’ holistic well-being, and continuous professional development and training for staff and faculty (Ngo & Hinojosa, 2021). The creation and staffing of Undocumented Student Resource Centers can also support these efforts (Cisneros & Valdivia, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education institutions also need to consider their own institutional policies and how they support undocumented students (Enriquez et al, 2019). With respect to the community college setting, specific recommendations for practice include flexible course offerings and requirements, access to clear and guiding information, access to psychological services that support undocumented students’ holistic well-being, and continuous professional development and training for staff and faculty (Ngo & Hinojosa, 2021). The creation and staffing of Undocumented Student Resource Centers can also support these efforts (Cisneros & Valdivia, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The creation and staffing of Undocumented Student Resource Centers can also support these efforts (Cisneros & Valdivia, 2020). Given the volatility of state and national political climates, it is critical to conduct additional research on inclusive policies and practices on campus that can support undocumented college students (Enriquez et al, 2019; Muñoz et al, 2018; Ngo & Hinojosa, 2021; Nienhusser, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, smaller institutions are more likely to have mental health offices open fewer than 12 months out of a year (Gorman et al., 2021). Students enrolled at 4‐year universities often have access to mental health services; however, the same may not be true for students enrolled at 2‐year institutions (Ngo & Hinojosa, 2021). For example, it has been found that 95% of community colleges have no contracted on‐site psychiatry services, compared to 59% of 4‐year institutions (Gallagher, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Culturally responsive services at mental health support centers are scarce in higher education institutions (Cha et al., 2019; Ngo & Hinojosa, 2021). In one study, undocumented students described that speaking with a counselor does not resolve underlying challenges related to their immigration status and may further increase their stress (Cha et al., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation